Fabrication and testing of GLARE specimens - Lim, Kendrick Zi Yang. (2012)
This report presents the results for the fabrication and testing of GLARE specimens. The mechanical properties were understood through the quasi-static tests and low velocity impact tests, and the results were compared with results obtained from Finite Element Method. This project also studied the difference in strength of GLARE specimens fabricated using different curing methods. The autoclave curing method was compared to the oven post-curing method using the quasi-static test and the oven post-curing method was found to be the better method. Specimens with the 2/1 configuration were compared to specimens with the 2/2 configuration. It was observed that an extra glass fiber layer in between the aluminum layers does not affect the impact performance of GLARE significantly.